MULTIMEDIA PEMBELAJARAN UNTUK PEMROGRAMAN TERSTRUKTUR MENGGUNAKAN PROBLEM-BASED LEARNING DENGAN KONSEP COMPUTATIONAL THINKING UNTUK MENINGKATKAN PEMAHAMAN SISWA - Dina Dwi Handayani, - (2021)
This study aims to increase students' understanding skills in structured programming disciplines by integrating a problem-based learning paradigm with web-based multimedia. Students are not accustomed to completing tasks in a logical and methodical manner; instead, they are accustomed to solving problems by entering values into formulas without first setting down what they know against the information they require. Computational stories in the form of problem-based narratives allude to real-world issues, and students seek solutions using the phases of computational thinking. Multimedia directs students through computational thinking techniques of abstraction, decomposition, pattern recognition, and algorithm design. This study uses a pre-experimental design that compares the results of the pretest and posttest in one group, conducted on class X students of SMK Negeri 1 Cimahi. From the results of the study, it was found that: 1) The learning media was "very good" with a percentage of 96.67 and the learning material was in the "very good" category with a percentage of 93%. 2) Learning media can improve computational thinking skills, which is marked by an increase in the average pre-test of 6.47 to the post-test results with an average of 58.02 and an n-gain of 0.55 which is included in the "medium" category. 3) Students respond in the category of "very good" to multimedia with a percentage of 90.42%.